Effect of different statins and EZETIMIBE/SIMVASTATIN on cardiovascular disease in patients with chronic kidney disease - ZHANG Xue-qing; Yiming·Muyesaier; Abualiti·Alimire; LU Chen (Linchuang shenzangbing zazhi)
Objective To explore the effect of different statins and EZETIMIBE/SIMVASTATIN on cardiovascular disease in patients with chronic kidney disease(CKD). Methods This study was a prospective study design and selected 503 cases of 3-5 phase CKD patients. The subjects were divided into simvastatin group,rosuvastatin group,atorvastatin group and EZETIMIBE/SIMVASTATIN group according to their medication history. The end of the event is the occurrence of cardiovascular disease. The Kaplan Meier model was used to verify the effect of the drugs on cardiovascular disease in patients with CKD. Results A total of 435 patients were followed up(104 in the simvastatin group,116 in the rosuvastatin group,112 in the atorvastatin group and 103 in the EZETIMIBE/SIMVASTATIN group). During the follow-up period,the incidence of cardiovascular disease in the four groups was 34. 9 %,33. 9 %,33. 3 % and 25. 4 %,respectively. Compared with the simvastatin group,the probability of cardiovascular disease in rosuvastatin and atorvastatin groups did not decrease significantly(with simvastatin as the reference,the HR of rosuvastatin group was 0. 98,95 % CI 0. 90-1. 04,P = 0. 10,and the HR of atorvastatin group was 0. 97,95 % CI 0.91-1. 04,P = 0. 30). The incidence of cardiovascular disease was significantly lower in EZETIMI-BE/SIMVASTATIN group than that in the rest groups(HR = 0. 59,95 % CI 0. 39-0. 76,P = 0.002). Conclusions Patients with chronic kidney disease treated with EZETIMIBE/SIMVASTATIN can obtain more satisfactory effects than other statins in reducing the incidence of cardiovascular diseases.